Interaction Between Economic Conditions and the Presence of Law: Case Study of the Impact of Legal Policy on Economic Growth in Indonesia - Supardi; Sriyono (International Conference On Law And Social Sciences, 2024)
This research analyzes the impact of legal policy on economic growth in Indonesia. Legal policies play an important role in shaping a country's business and investment climate, which in turn influences economic growth. Therefore, understanding how the interaction between economic conditions and the presence of law affects economic growth is very important. The main objective of this research is to analyze the impact of legal policies on economic growth in Indonesia, taking into account factors such as market regulation, protection of intellectual property rights, and law enforcement. The research methodology used is a case study with a qualitative approach. Data was obtained through analysis of policy documents, interviews with economic and legal experts, as well as a review of relevant literature. The results of the analysis show that legal policies that focus on increasing legal certainty, protecting intellectual property rights, and effective law enforcement have a positive impact on economic growth in Indonesia. However, challenges such as corruption, policy inconsistencies, and slow bureaucracy affect the effectiveness of legal policies and their impact on economic growth. In conclusion, this study highlights the importance of harmonization between economic and legal policies in creating a business climate that is conducive to sustainable economic growth in Indonesia. Practical implications of this research include the need for further legal reform, increased transparency, and strengthening law enforcement institutions to support sustainable economic growth. In accordance with SDGs no. 8, namely Decent Work and Economic Growth.